Left atrial appendage occlusion in patients with end-stage renal disease: an individual patient-level meta-analysis - Rodriguez-Riascos, Juan F.; Vemulapalli, Hema S; Akın, Ibrahim; Areiza, Luis A; Della Rocca, Domenico G; Eitel, Ingo; Fink, Thomas; Genovesi, Simonetta; Kefer, Joelle; Zweiker, David; Prajapati, Poojan; Srivathsan, Komandoor (Europace, 2025)
Patients with end-stage renal disease (ESRD) and atrial fibrillation present a challenge for thromboembolic prevention, given their elevated risks of both thromboembolism and bleeding. Anticoagulants carry a higher bleeding risk in this population without clear evidence of thromboembolic benefit. This study aims to define the role of left atrial appendage occlusion (LAAO) as a preventive strategy for patients with ESRD.A systematic literature review was conducted to identify studies reporting outcomes in patients with ESRD who underwent LAAO. Meta-analyses of aggregate and individual patient data were performed to evaluate acute and long-term outcomes and compare them with those of patients without ESRD. Seventeen studies reporting data from 24 127 patients, including 1047 with ESRD, were included. Procedural complications were more common in patients with ESRD (RR 2.23; P = 0.02), with a pooled rate of 4% (95% CI, 1-9%). There was no significant difference in thromboembolic event rates during follow-up between the groups (IRR 1.44; P = 0.16), but major bleeding incidence was higher among patients with ESRD (IRR 1.84; P < 0.01). Individual patient-level data from seven studies comprising 4745 patients (268 with ESRD) were obtained and analysed. Similarly, there was no significant association between ESRD and stroke/TIA incidence (HR, 1.22; 95% CI, 0.66-2.26), but major bleeding was higher on patients with ESRD (HR, 1.65; 95% CI, 1.01-2.69).LAAO represents a feasible option for thromboembolic prevention in patients with ESRD, although these patients have an increased risk of complications and bleeding.